Lemierre's Syndrome Due to Methicillin-Resistant - Rolando A. Zamora Gonzalez MD; Juan C. Sarria MD, FIDSA; Nicole A. Christians MD; Michelle Baliss DO (SAGE Publishing, 2019)
Lemierre's syndrome is an uncommon and potentially fatal complication of oropharyngeal and facial infections. It involves an associated septic thrombophlebitis, bacteremia, and septic emboli. Traditionally, compromise of the internal jugular vein has been described in conjunction with an infection caused by anaerobes, especially, Fusobacterium necrophorum . In recent years, however, variant forms have been appearing, including other vessel compromise and other etiologic agents. We present the case of Lemierre's syndrome in a 31-year-old male with facial vein thrombosis, septic emboli to the lungs, and bacteremia caused by methicillin-resistant Staphylococcus aureus. We hope that this case will raise awareness about variant presentations and promote a timely diagnosis and appropriate treatment of this potentially fatal infection.